The challenge of vector development in gene therapy - S.U. Dani (Brazilian Journal of Medical and Biological Research, 1999)
Gene therapy is the treatment of diseases based on the transfer of genetic information. Agents that carry or deliver DNA to target cells are called vectors (Latin vector: carrier, deliverer). Ideally, a vector should accommodate an unlimited amount of inserted DNA, lack the ability of autonomous replication of its own DNA, be easily manufactured, and be available in concentrated form. Secondly, it should have the ability to target specific cell types or to limit its gene expression to specific cell types, and to achieve sustained gene expression in the long term or in a controlled fashion. Finally, it should not be toxic or immunogenic. Such a vector does not exist and none of the DNA delivery systems so far available for in vivo gene transfer is perfect with respect to any of these points. Gene therapy and the means to promote it depend heavily on the development and improvement of new gene vector systems.